Pertahanan Maritim: Antisipasi Ancaman Militer Melalui Kolaborasi Sumber Daya Nasional - Sumarlin, Sumarlin; Adriyanto, Agus; Warka, I Wayan (AGUSPATI Research Institute, 2023)
The increasing complexity of military threats in the maritime domain highlights the need for an integrated and collaborative approach in developing effective defense strategies. There is a requirement for in- depth analysis of the maritime defense concept, emphasizing the anticipation of military threats through the optimization of collaboration with national resources. This is supported by the identification of national resources, including human, natural, and artificial resources, as key elements in strengthening naval defense. The conceptual framework involving all main defense components, namely the Indonesian Navy (TNI AL), reserve components, and supporting components, has implications for the success of military defense. This collaboration is described as a comprehensive effort involving community empowerment, coordination of relevant sectors, and capacity building in facing evolving maritime threats. Case studies and examples of the implementation of this strategy are presented to support a practical understanding of the success of national resource collaboration in the context of maritime defense. Research findings indicate that collaboration with national resources not only strengthens military resilience but also expedites responses to threats. Therefore, this article provides policy recommendations to optimize cross-sector cooperation, involve communities, and enhance human resource capacity. As a contribution to strategic thinking in maritime defense, this article is expected to offer practical guidance for policymakers, practitioners, and academics engaged in national security and maritime defense.